2022
DOI: 10.1002/jmv.28002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the respiratory tract microbiome in hospitalized COVID‐19 patients with different disease severity

Abstract: Background: Little is known about the characteristics of respiratory tract microbiome in Coronavirus disease 2019 inpatients with different severity. Methods: A cross-sectional study was conducted to characterize respiratory tract microbial communities of 69 COVID-19 inpatients from 64 nasopharyngeal swabs and 5 sputum specimens using 16S ribosomal RNA (rRNA) gene V3-V4 region sequencing. The bacterial pro les were used to nd potential biomarkers by the two-step method, the combination of random forest model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
5
23
0
Order By: Relevance
“…Alloprevotella was found as one of the community types of oropharyngeal microbiota in patients with COVID‐19 infection, 26 and the enriched Alloprevotella identified in COVID‐19 patients was an inflammation‐associated microbe that had a positive correlation with serum levels of C‐reactive protein 27 . Alloprevotella was also identified in another study as a potential microbial biomarker to distinguish mild COVID‐19 patients from severe COVID‐19 patients 28 . In the MR analyses, we found that fecal Alloprevotella could causally increase COVID‐19 susceptibility by 1.08‐fold but had no causal effects on severe virus‐related symptoms.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Alloprevotella was found as one of the community types of oropharyngeal microbiota in patients with COVID‐19 infection, 26 and the enriched Alloprevotella identified in COVID‐19 patients was an inflammation‐associated microbe that had a positive correlation with serum levels of C‐reactive protein 27 . Alloprevotella was also identified in another study as a potential microbial biomarker to distinguish mild COVID‐19 patients from severe COVID‐19 patients 28 . In the MR analyses, we found that fecal Alloprevotella could causally increase COVID‐19 susceptibility by 1.08‐fold but had no causal effects on severe virus‐related symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…27 Alloprevotella was also identified in another study as a potential microbial biomarker to distinguish mild COVID-19 patients from severe COVID-19 patients. 28 In the MR analyses, we found that fecal disease and colorectal cancer. 29 Higher levels of Erysipelotrichaceae were also associated with higher BMIs which have also been a risk factor to causally increase COVID-19 risks.…”
Section: Validation Of Microbial Biomarkers Of Covid-19mentioning
confidence: 89%
“…However, the specific microbiome changes that have been associated with severity vary among studies. Together, these early findings suggest that the airway microbiome may be an important factor in indicating or influencing COVID‐19 clinical outcomes and should be investigated further 17,20,21 …”
Section: Introductionmentioning
confidence: 94%
“…Another controversial question is whether COVID-19 patients could present an increased abundance of pathobionts in the nasopharynx that may result in a higher incidence of secondary bacterial infections and aggravate pneumonia. Regarding this, although Chen and colleagues, who analyzed nasopharyngeal swabs from 64 hospitalized COVID-19 patients with different disease severities, found that severe patients had lower abundance of opportunistic pathogens compared to mild patients, including the bacterial genera Actinomyces , Prevotella , Rothia , Streptococcus , and Veillonella (Table S1) [ 56 ], the majority of studies analyzing this issue support the idea that SARS-CoV-2 infection alters the symbiosis between commensal bacteria and opportunistic pathogens that are present in the nasopharynx, resulting in an over-proliferation of pathogenic bacteria that predispose to the development of comorbidities (Table S1) [ 50 , 52 , 55 , 66 , 71 ]. In this regard, Bai and colleagues reported an increased abundance of pathogenic bacteria in critically ill COVID-19 patients compared to uninfected subjects (Table S1) [ 52 ].…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%